Mandibular (Gnathic) osteosarcoma: Narrative review emphasizing clinical, radiological, and histopathological correlation - Praveen K. Sharma; Iffath Misbah; J.H.Shazia Fathima; Ajay Lucas Rubben; Jeban Chella Bruce (Oral Oncology Reports)
Background: Mandibular (Gnathic) osteosarcoma, a rare form of primary bone cancer, presents unique challenges due to its location and the essential functions of the mandible. This review aims to synthesize current knowledge on mandibular osteosarcoma, highlighting its clinical presentation, diagnostic challenges, and treatment strategies. Methods: A comprehensive literature review focused on recent studies and reviews on mandibular osteosarcoma. Epidemiology, clinical presentation, diagnostic methods, and advances in treatment modalities were among the main topics of study. Discussion: Mandibular osteosarcoma typically presents as a painless swelling or a painful mass in the jaw, often leading to a delayed diagnosis due to its nonspecific symptoms. Radiographic imaging plays a crucial role in diagnosis, supplemented by histopathological examination. Treatment primarily involves surgical resection, which can range from limb-sparing surgery to radical resection, depending on tumor size and location. Post-operative reconstruction is essential for restoring function and aesthetics. Chemotherapy is a critical adjunct to surgery, while radiation therapy is reserved for specific cases. The multidisciplinary approach to treatment planning is emphasized for optimal patient outcomes. Conclusion: Early diagnosis and a tailored treatment approach are essential for improving the prognosis of mandibular osteosarcoma. Improvements in adjuvant therapies and surgical procedures have improved the results of treatment. Nonetheless, the illness's rarity highlights the necessity of continued study and teamwork to comprehend and successfully treat this complicated cancer.